PEMBERDAYAAN MASYARAKAT MELALUI PENGEMBANGAN DESA WISATA KANDRI, KECAMATAN GUNUNGPATI, KOTA SEMARANG - Wandira Naibaho,; Herbasuki Nurcahyanto; Aufarol Marom (Journal of Public Policy and Management Review, 2023)
Community empowerment through the development of Kandri Tourism Village, Gunungpati District, Semarang City is based on increasing empowerment efforts to improve the economy, welfare and standard of living of the people of Kandri Tourism Village. The problems of this research are that the management system is not fully structured and optimally organized, problems with the quality of the physical environment and limited infrastructure, lack of outreach or training, and lack of government and community involvement in empowerment. The purpose of this research is to analyze empowerment efforts and the inhibiting factors for the sustainability of empowerment. Efforts to answer the problems and research objectives use the Community Empowerment theory put forward by Mardikanto by using descriptive research methods and qualitative approaches. The data obtained in this study through interviews, observation, and documentation. The results of the study show that community empowerment through the development of the Kandri Tourism Village, Gunungpati District, Semarang City has made good empowerment efforts. This can be seen from the 4 indicators, namely human development, business development, environmental development, and institutional development. Empowerment efforts in Kandri Tourism Village have not been fully achieved because there are several obstacles that occur, namely limited involvement and quality of human resources, limited facilities and infrastructure, and limited physical environmental conditions. It is suggested to the Pandanaran Tourism Awareness Group (POKDARWIS) to be able to increase the role of the Government and the Community, increase the availability of infrastructure, improve the quality of the physical environment so that community empowerment in Kandri Tourism Village can be carried out optimally.